The Integrative Curriculum Management with a Boarding System in High Schools - Riza Ashari; Chandra Sukrisna; Agus Budiman; Azmi Zarkasyi; Muh Barid Nizarudin Wajdi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research addresses the pressing need for an integrated madrasah-Islamic boarding school curriculum as a strategic response to the contemporary challenges demanding graduates with both extensive knowledge and profound religious understanding. With the imperative for cognitive and spiritual intelligence in the disruptive era, the study focuses on MAN 2 Malang City, utilizing a qualitative case study approach involving observations, interviews, and document analysis. The research reveals essential aspects of the integrated curriculum, encompassing unified objectives and organized content planning. The implementation phase includes the integration of academic calendars and a structured supervision framework. The study also emphasizes the significance of an evaluative process covering contextual, input, process, and outcome dimensions. Ultimately, this research underscores the critical role of an integrated curriculum in nurturing well-rounded individuals equipped to navigate the complexities of the modern world, offering valuable insights for educational practitioners and policymakers.